Modeling light interception and distribution in mixed canopy of common cocklebur (Xanthium stramarium) in competition with corn Modelagem de interceptação e distribuição de luz em dossel de xanthium stramarium em competição com milho - F. Vazin; M. Hassanzadeh; A. Madani; M. Nassiri-Mahallati; M. Nasri (Planta Daninha, 2010)
The aim of this study was to model light interception and distribution in the mixed canopy of Common cocklebur (Xanthium stramarium) with corn. An experiment was conducted in factorial arrangement on the basis of randomized complete blocks design with three replications in Gonabad in 2006-2007 and 2007-2008 seasons. The factors used in this experiment include corn density of 7.5, 8.5 and 9.5 plants per meter of row and density of Common cocklebur of zero, 2, 4, 6 and 8 plants per meter of row. INTERCOM model was used through replacing parabolic function with triangular function of leaf area density. Vertical distribution of the species' leaf area showed that corn has concentrated the most leaf area in layer of 80 to 100 cm while Common cocklebur has concentrated in 35-50 cm of canopy height. Model sensitivity analysis showed that leaf area index, species' height, height where maximum leaf area is seen (hm), and extinction coefficient have influence on light interception rate of any species. In both species, the distribution density of leaf area at the canopy length fit a triangular function, and the height in which maximum leaf area was observed was changed by change in density. There was a correlation between percentage of the radiation absorbed by the weed and percentage of corn seed yield loss (r² = 0.89). Ideal type of corn was determined until the stage of tasseling in competition with weed. This determination indicates that the corn needs more height and leaf area, as well as less extinction coefficient to successfully fight against the weed. O objetivo deste estudo foi desenvolver um modelo de intercepção de luz e distribuição na copa mista do cardo comum (Xanthium stramarium) com o milho. Um experimento foi conduzido em arranjo fatorial com base no projeto de blocos completos randomizados com três replicações em Gonabad nas estações de 2006-2007 e 2007-2008. Os fatores usados neste experimento incluem a densidade do milho de 7,5, 8,5 e 9,5 plantas por metro de linha e densidade do cardo comum de zero, 2, 4, 6, e 8 plantas por metro de linha. O modelo INTERCOM foi usado através da substituição da função parabólica com função triangular da densidade da área da folha. A distribuição vertical da área das folhas das espécies mostrou que o milho concentrou a maior área foliar em camada de 80 a 100 cm enquanto o cardo comum concentrou em 35-50 cm de altura de copa. A análise da sensibilidade do modelo mostrou que o índice da área da folha, altura das espécies, altura onde a área máxima da folha é vista (hm), e coeficiente de extinção tem influência sobre a taxa de intercepção da luz em qualquer uma das espécies. Nas duas espécies, a densidade da distribuição da área da folha no comprimento da copa adequou-se a uma função triangular, e a altura na qual a área máxima da folha foi observada foi mudada pela mudança na densidade. Houve uma correlação entre a porcentagem da radiação absorvida pelas plantas daninhas e a porcentagem de perda de rendimento da semente do milho (r² = 0,89). O tipo ideal de milho foi determinado até o estágio de borlamento em competição com plantas daninhas. Esta determinação indica que o milho necessita de mais altura e área foliar, assim como de menos coeficiente de extinção para lutar com sucesso contra as plantas daninhas.